Pleomorphic adenoma of the upper lip: A case report - Aida, Junko; Katada, Ryogo; Nemoto, Yuki; Nemoto, Tetsuo; Sato, Hitoshi; Ito, Mirii; Kojima, Keijirou; Shirota, Tatsuo (Journal of the Showa Medical University, 2025)
Pleomorphic adenoma is the most common benign tumor of the salivary glands. It typically occurs in the parotid gland but rarely on the lips. Here, we report a case of pleomorphic adenoma of the upper lip. The patient, a man, had been aware of a mass on his right upper lip for 10 years but ignored it because he had no other symptoms. The mass gradually increased in size. Therefore, the patient was referred to our department. On clinical examination, an 11-mm, clear, mobile, painless, and firm mass with an elastic consistency was noted on the mucosal surface of the right upper lip. The overlying mucosa appeared normal. Magnetic resonance imaging revealed low signal intensity on T1-weighted images and high signal intensity on T2-weighted images, with a heterogeneous internal structure. The tumor was surgically excised under general anesthesia in January 2023. Histopathological examination confirmed the diagnosis of pleomorphic adenoma. Six months after surgery, the patient exhibited no signs of lip dysesthesia, dyskinesia, or tumor recurrence, and his condition remained stable. Herein, we describe a pleomorphic adenoma of the upper lip.